Electrophysical characteristics of power MOSFETs additionally implanted with nitrogen ions - Odzaev, Vladimir B.; Pyatlitski, Aliaksandr N.; Prasalovich, Uladislau S.; Kovalchuk, Natalya S.; Soloviev, Yaroslav A.; Shestovski, Dmitry V.; Yavid, Valentin Yu.; Yankovski, Yuri N. (Journal of the Belarusian State University. Physics, 2022)
The electrical characteristics of power MOSFETs additionally implanted with nitrogen ions have been studied. Ion implantation of nitrogen was carried out through a protective oxide of 23 nm thickness with energies of 20 and 40 keV and doses of 1 ⋅ 1013‒5 ⋅ 1014 cm–2. Rapid thermal annealing was carried out at temperature of 900 or 1000 °C for 15 s. It has been established that nitridisation of the gate dielectric makes it possible to reduce the noise of the gate leakage currents and their dispersion. In the direct order of heat treatment (first rapid thermal annealing, and then the removal of the protective oxide), for samples prepared with an additional operation of nitrogen ion implantation, there is an increase in the threshold voltage compared to control samples. The capacitance of the gate dielectric in the case of implantation of nitrogen ions in the direct order of heat treatment is less than for control samples. It has been established that in the direct order of rapid thermal annealing, the doses of nitrogen ion implantation do not cause significant changes in the maximum value of the current-voltage slope. At the same time, in all studied cases, there is a shift in the maximum value of the current-voltage slope towards higher gate voltages. In the reverse order of heat treatment (first the removal of the protective oxide, and then rapid thermal annealing), there are no significant differences in the value of the threshold voltage for the samples created with additional nitrogen implantation and the control ones. The maximum value of the current-voltage slope also does not experience significant changes. It is shown that in the voltage range from – 0.15 to 0 V, the drain current of nitrogen-implanted samples manufactured using the direct order of heat treatment is higher than for control samples, and the drain current of nitrogen-implanted samples obtained with the reverse order of heat treatment it is lower compared to control samples. Results are explained by a decrease in the density of surface states at the Si – SiO2 interface in MOS-structures created using an additional operation of nitrogen ion implantation in the direct order of heat treatment.
Keywords: gate dielectric; ion implantation; nitrogen ions; power MOSFETs